Pengaruh Kejelasan Sasaran Anggaran, Desentralisasi, Ketidakpastian Lingkungan, Dan Sistem Akuntansi Manajemen Terhadap Kinerja Manajerial (Studi Empiris Pada Kantor Pelayanan Perbendaharaan Negara Pekanbaru) - Yetti, Febri Delmi; Putri, Anisa Ika (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This study aims to examine the direct effect of the variables of budget targets clarity, decentralization, environmental uncertainty and management accounting system on managerial performance. This study was conducted at the Pekanbaru State Treasury Service Office. The population in this study were employees working at the Pekanbaru State Treasury Service Office totaling 42 people. The sampling technique used was purposive sampling. The respondents in this study were the head of the office as the user of the budget/goods, the head treasurer and employees. The sample used in this study was 42 respondents. The statistical method used to test the research hypothesis is multiple linear regression analysis using SPSS software version 29.0. The results of the study indicate that the variables of budget target clarity,decentralization, environmental uncertainty and management accounting systems have an effect on managerial performance. The magnitude of the influence of R-Square (R2) from budget target clarity, decentralization, environmental uncertainty and management accounting systems on managerial performance is 28.9% while the remaining 71.1% is influenced by other independent variables not examined in this study.